Diary of a worm - Cronin, Doreen; Bliss, Harry, 1964- ([New York] : Joanna Cotler Books, 2003)
A young worm discovers, day by day, that there are some very good and some not so good things about being a worm in this great big world.
On the title page, the i in the word diary is represented by a pencil. The o in the word worm is represented by a worm.
Book Links (A.L.A.)
School Library Journal starred
Wilson's Children
Book Links (A.L.A.), July 2007
Bulletin (Center for Children's books), October 2003
Keywords: Diaries -- Fiction; Worms -- Fiction; Diaries -- Fiction; Worms -- Fiction